SISTEM INFORMASI PENJADWALAN SOPIR BUS SAFARI DHARMA RAYA BERBASIS SMS GATEWAY (Information Technology and Telematics, 2013)
Abstract : The  use  of  SMS  can  be  used  to  provide  information quickly and precisely because in addition to easy to  use is also less costly .. Safari Dharma Raya is a company engaged in  the  field  of  freight  transportation  service buses in Temanggung and the surrounding  area.  The   number  of drivers on the PO. Safari Dharma Raya  greater than the number of existing bus,so the driver needs to  there is scheduling work so that the performance of the company to be optimal At this time the driver  must come to the office every day to see the  schedule of buses ordered items are written on the bulletin board.The purpose of this research is to create an information system for bus driver scheduling Safari Dharma Raya holidays. Use of a computer device that is connected to the GSM modem can be used to send mass SMS. Gammu module settings can be done by using the website pages using PHP programming language. Mass SMS sending is done in a sequence corresponding phone number listed on a database table with a lag time of delivery driver about a minute.Keywords: Scheduling Driver, Tourist Bus, SMS Gateway